Quality of Life and Quality of Support for People with Severe Intellectual Disability and Complex Needs. Issue 5 (22nd May 2015) - Beadle‐Brown, J.; Leigh, J.; Whelton, B.; Richardson, L.; Beecham, J.; Baumker, T.; Bradshaw, J.
Abstract : Background: People with severe and profound intellectual disabilities often spend substantial time isolated and disengaged. The nature and quality of the support appears to be important in determining quality of life. Methods: Structured observations and staff questionnaires were used to explore the quality of life and quality of support for 110 people with severe and profound disabilities and complex needs. Results: On average, people spent approximately 40% of their time engaged in meaningful activities, received contact from staff 25% of the time (6% in the form of assistance to be engaged). Just over one‐third received consistently good active support, which was associated with other measures of quality of support and emerged as the strongest predictor of outcomes. Conclusions: Quality of life and quality of support were relatively poor, although with about one‐third of people receiving skilled support. Consistently good active support was the best predictor of outcome and proposed as a good indicator of skilled support.